Supply Chain Practices and Marketing Performance of SMEs: A Field Study on Furniture Manufacturing in Egypt - Said, Yasser (Archives of Business Research, 2021)
The study aimed to investigate the effect of supply chain practices on the marketing performance of small and medium-sized furniture manufacturing enterprises in Egypt. The study applied to 67 enterprises in Damietta, Egypt. Accordingly, the study population was represented by two top directors of furniture companies either. Two 39-item- questionnaires of a five-point Likert-type scale were used for each enterprise with a total of 134 questionnaires. Internal consistency of 120 valid questionnaires by using Pearson correlation revealed that the questionnaire was stable and valid. Descriptive statistics for all items of the questionnaire were carried out. The relationship between supply chain practices and marketing performance by Pearson correlation revealed there was a positive relationship between supply chain practices parameters; (supplier relationship management, intermediaries and distributers’ relationship management, and customer relationship management) and marketing performance. The correlation coefficients of marketing performance were 0.609, 0.539, and 0.794, respectively. Estimation of differences in supply chain practices and marketing performance by one-way ANOVA and T-test revealed significant differences (p < 0.05) in age and size of the capital of supply chain and job title and experience of marketing performance. In conclusion, this study provides the top managers in SMEs the power to make decisions under normal and abnormal circumstances, as in the COVID 19 crisis, which may be crucial in the survival and existence of SMEs.